The Hypertension Paradox: Survival Benefit After ST-Elevation Myocardial Infarction in Patients With History of Hypertension. A Prospective Cohort- and Risk-Analysis - Hoffmann, Fabian; Fassbender, Patricia; Zander, Wilhelm; Ulbrich, Lisa; Kuhr, Kathrin; Adler, Christoph; Halbach, Marcel; Reuter, Hannes (Frontiers in Cardiovascular Medicine, 2022)
Background Mortality after ST-elevation myocardial infarction (STEMI) is dependent from best-medical treatment after initial event. Objectives Determining the impact of prescription of guideline-recommended therapy after STEMI in two cohorts, patients with and without history of arterial hypertension, on survival. Methods 1,025 patients of the Cologne Infarction Model registry with invasively adjudicated STEMI were dichotomized according to their history of arterial hypertension. We recorded prescription rates and dosing of RAS-inhibitors, β-blockers and statins in all patients. The primary outcome was all-cause death. Mean follow-up was 2.5 years. Results Mean age was 64 ± 13 years, 246 (25%) were women. 749 (76%) patients had a history of hypertension. All-cause mortality was 24.2%, 30-day and 1-year mortality was 11.3% and 16.6%, respectively. History of hypertension correlated with lower mortality (hazard ratio [HR], @30 days: 0.41 [0.27-0.62], @1 year: 0.37 [0.26-0.53]). After adjusting for age, sex, Killip-class, diabetes mellitus, body-mass index, kidney function and statin prescription at discharge 1-year mortality HR was 0.24 (0.12-0.48). At discharge, prescription rates for RAS-inhibitors, β-blockers and statins, as well as individual dosing and long-term persistence of RAS-inhibitors were higher in patients with history of hypertension. On the same lines, prescription rates for RAS-inhibitors, β-blockers and statins at discharge correlated significantly with lower mortality regardless of history of hypertension. Conclusion Patients with history of hypertension show higher penetration of guideline recommended drug therapy after STEMI, which may contribute to better survival. Better tolerance of β-blockers and RAS-inhibitors in patients with history of hypertension, not hypertension itself, likely explains these differences in prescription and dosing.